An investigation into relationships between supervisory leadership style and employee engagement in the City of Ekurhuleni Disaster and Emergency Management Services - Koch, Hayden Mark Adrian (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPA)--Stellenbosch University, 2023.